(untitled) (The Pakistan Development Review, 2012)
In this book, Ernst G. Frankel has reviewed development programmes, plans and agendas, initiated by the developed world for the developing countries. He has recounted numerous examples from the developing world to provide a well-structured commentary, which helps the reader to appraise the practical application of development theory, development financing and development management over the last fifty years. Author has himself been involved in development projects and missions for a long time therefore, he explicitly accounts for the causes of the enormous failures and the meagre success rate of development projects. He primarily forms his argument on the call of incorrect perception of local context and thus inappropriate planning, funding and implementation of development projects. Overall, he has taken an unconventional view of development and making development happen. He describes development as a dynamic process, which is flexible and iconoclastic in nature and, thus, should incorporate the mutable nature of human behaviour, culture, science and technology over time.